2006
DOI: 10.1007/s10162-006-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Abundant COL9A1 Transcript in the Cochlea with a Novel 3′ UTR: Expression Studies and Detection of miRNA Target Sequence

Abstract: EST N66408 represents one of several large unique clusters expressed in the Morton human fetal cochlear cDNA library. N66408 is 575 bp in size and initial BLAST analysis of this sequence showed no homology to any known genes or expressed sequence tags (ESTs) from other organs or tissues. Sequence of the original cochlear clone from which N66408 was derived revealed that the corresponding cDNA was about 700 bp in size, including 125 bp at its 5 0 end with homology to the 3 0 end of COL9A1 in addition to 575 bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Although miRNA function in development and maintenance of the inner ear is just beginning to be explored, studies already suggest that their genetic regulatory properties are essential to the proper establishment of sensory neurons and sensory epithelial supporting and hair cells. Moreover, a study of miRNA expression during hair cell regeneration in newt sensory epithelia suggest a role for let-7 miRNAs in the process (Tsonis et al, 2007), and miR-9 function has been suggested in the regulation of a COL9A1 expression in human cochlea (Sivakumaran et al, 2006). Many questions remain regarding the functional contributions and mechanistic actions of individual miRNAs amidst the complexity of genetic and biochemical interactions that contribute to development, differentiation, and maintenance of specific cell types throughout the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Although miRNA function in development and maintenance of the inner ear is just beginning to be explored, studies already suggest that their genetic regulatory properties are essential to the proper establishment of sensory neurons and sensory epithelial supporting and hair cells. Moreover, a study of miRNA expression during hair cell regeneration in newt sensory epithelia suggest a role for let-7 miRNAs in the process (Tsonis et al, 2007), and miR-9 function has been suggested in the regulation of a COL9A1 expression in human cochlea (Sivakumaran et al, 2006). Many questions remain regarding the functional contributions and mechanistic actions of individual miRNAs amidst the complexity of genetic and biochemical interactions that contribute to development, differentiation, and maintenance of specific cell types throughout the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2006 when miRNAs appeared in the mammalian inner ear field, they have exploded as an additional layer of gene regulation in both inner ear development and disease (172). miRNAs show particular expression patterns in the inner ear.…”
Section: Mirnas Regulation Of Nihlmentioning
confidence: 99%
“…Splicing independent alternative polyadenylation produces transcript isoforms with 3' UTRs of different lengths, containing a constitutive segment and an alternative segment. If a microRNA target is located within the alternative part of the 3' UTR, the shorter transcript should be target free and should escape microRNA-mediated inhibition, while the longer transcript should be inhibited (47)(48)(49). Such variations are very common.…”
Section: Microrna Targets In Alternative 3' Utrsmentioning
confidence: 99%